PENGHITUNGAN JUMLAH POB (PERSONNEL ON BOARD) DI FASILITAS ANJUNGAN LEPAS PANTAI BERBASIS COMPUTER VISION - Darwis, Akbar; Tamaji (Universitas Widya Kartika Surabaya, 2024)
This paper will discuss about the use of computer vision technology in calculating the number of people entering and leaving wellhead facilities. In general, offshore platform facilities are divided into 2 (two) types, namely wellhead facilities and processing facilities. Limiting the number of people in wellhead facilities is closely related to the availability of safety devices and evacuation equipment in emergency conditions. This limitation is occur with a strong reason, considering that at wellhead facilities there are some of dangers that have the potential to harm workers, including: high pressure, toxic gas, flammable gas and high temperature. This research is case research and field research, where from the problems that occur in the field, data will be collected in the form of solutions that have been implemented, further be analyzed and put forward better and more efficient solutions (in this case utilizing computer vision technology).